2018
DOI: 10.3354/meps12690
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bottom trawling and primary production on the composition of biological traits in benthic assemblages

Abstract: 12

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 80 publications
1
17
0
Order By: Relevance
“…This study analyses a dataset described by Howarth et al (2018b) and available from (Howarth et al 2018a). In brief, trawling intensity (quantified as the swept-area-ratio, SAR (y -1 ), from Vessel Monitoring Systems data) and primary production (PP, mg C m -2 yr -1 , estimated by the MODIS satellite sensor) for the United Kingdom were divided into four categories (divided at equal intervals on a log scale for trawling intensities, and equal intervals on a natural scale for PP, Table 1).…”
Section: Samplingmentioning
confidence: 99%
See 4 more Smart Citations
“…This study analyses a dataset described by Howarth et al (2018b) and available from (Howarth et al 2018a). In brief, trawling intensity (quantified as the swept-area-ratio, SAR (y -1 ), from Vessel Monitoring Systems data) and primary production (PP, mg C m -2 yr -1 , estimated by the MODIS satellite sensor) for the United Kingdom were divided into four categories (divided at equal intervals on a log scale for trawling intensities, and equal intervals on a natural scale for PP, Table 1).…”
Section: Samplingmentioning
confidence: 99%
“…A retrospective multivariate analysis of the environmental variables at the sampling stations indicated that the environmental conditions at two stations were dissimilar to the others based on their sediment particle size distribution (with very low and very high mean sediment particle sizes respectively). These were excluded from further analyses (details in Howarth et al 2018b). Hence, data are missing for the combination of low trawling and moderately high primary production.…”
Section: Samplingmentioning
confidence: 99%
See 3 more Smart Citations